2021
DOI: 10.1002/er.6956
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in hierarchical anode designs of TiO2‐B nanostructures for lithium‐ion batteries

Abstract: The state-of-the-art development progress of the fabrication, design, modification, and applications of TiO 2 -B-based hierarchical nanostructures with a wellcontrolled size and morphology in lithium-ion battery (LIB) applications has been summarized and discussed. Based on studying on lithiation/delithiation on mechanisms of a typical metal oxide nanomaterials, along with doping with foreign atoms (metal or non-metal), using electronically conductive additives (graphene/graphene derivatives), as well as desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 192 publications
(418 reference statements)
0
6
0
Order By: Relevance
“…These observations also implied that the surface distortion of TIO180_12 was more common, resulting in faster Li diffusion. 18 Nevertheless, the differences in D Li from each material were not significantly distinctive and has not influenced much during cycle performance tests.…”
Section: Electrochemical Measurementmentioning
confidence: 85%
See 1 more Smart Citation
“…These observations also implied that the surface distortion of TIO180_12 was more common, resulting in faster Li diffusion. 18 Nevertheless, the differences in D Li from each material were not significantly distinctive and has not influenced much during cycle performance tests.…”
Section: Electrochemical Measurementmentioning
confidence: 85%
“…), were compared with TiO 2 (B) in the literature, as illustrated in Table S1. It was found that carbon-based materials have a specific capacity close to TiO 2 (B) (theoretical specific capacity 335 mAh/g) , including graphene, which has two faces on the 2-dimensional carbon sheets. However, graphene has some disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…As an anode for lithium-ion batteries, TiO 2 has been widely studied due to its good structural and cyclic stability, long cycle life, good safety, and low cost. The bronze phase TiO 2 (TiO 2 (B)) has the highest theoretical capacity since it has the lowest density among TiO 2 polycrystals. Moreover, it has been reported that the magnesium borohydride/tetraglyme electrolyte, , PhMgCl-AlCl 3 + LiCl/THF electrolyte and an all-phenyl complex/THF electrolyte , can be matched with TiO 2 and a Mg-metal electrode, although the options are limited. However, because of the poor mobility of Mg 2+ and the low conductivity of TiO 2 due to the wide band gap (about 3.2 eV), , experiments show that TiO 2 (B) is difficult to be inserted by Mg ions and exhibits low circulation capacity. ,, In addition, TiO 2 (B) has also been reported that when it is used as MIB electrode, it is mainly based on a pseudo capacitive reaction of surface storage, which does not involve the dis/insertion of ions within the host material and shows 110 mAh g –1 at the 0.1C rate. , Therefore, it is necessary to discuss whether the existing modification means can make TiO 2 a reversible MIB electrode by enhancing its performance.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Since the discovery of photochemical water splitting using titania (TiO 2 ) electrode in 1972, [13] this environmentally benign, cost-effective oxide has become the most used semiconducting material as photocatalyst. [14] Due to its surface, electronic and photocatalytic properties it has been used in the fields of photochemical dye degradation [15] , fuel cell [16] , lithium ion batteries [17] and biosensors [18] . In the current study, the anatase form of TiO 2 has been preferred over its other polymorphs because of its highest electron mobility.…”
Section: Introductionmentioning
confidence: 99%